Porous material for generating power by utilizing moisture as well as preparation method and application of porous material
By using porous materials prepared by modified fabric coated with MXene, PSS and xanthan gum mixture in the moisture power generation equipment, the problems of low moisture adsorption efficiency and material aging in the prior art are solved, and efficient and stable moisture power generation performance are achieved.
Patent Information
- Application Number
- CN202510085959.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The adsorption efficiency of existing moisture power generation equipment materials on water molecules is low, resulting in weakening of power generation effect, and structural aging or performance decline is prone to long-term humidity exposure, shortening the service life of the equipment.
Porous materials are prepared using modified fabrics coated with mixtures of MXene, PSS and xanthan gum. Through its highly developed pore structure and molecular-level hygroscopic properties, the moisture absorption efficiency and stable output of electrical energy.
It realizes high current and voltage output, the output performance can be maintained for a long time, the preparation cost is low, the process is simple, and it is suitable for energy harvesting in various humidity environments.
Smart Images

Figure CN119877269A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy, and in particular relates to a porous material for generating electricity using moisture, and a preparation method and application thereof. Background Art
[0002] In the past decade, with the rapid development of new energy material science and micro-nanotechnology, wet gas generators, as an emerging environmental energy harvesting technology, provide innovative possibilities for capturing water vapor from the air and converting it into electrical energy. They generate electricity through moisture-driven power and are adaptable to a variety of environments, especially in areas without electricity supply or in remote areas.
[0003] Common wet gas generators include those based on nanomaterials such as carbon nanotubes, graphene, and conductive polymers to achieve energy conversion. These devices can effectively absorb water molecules in an environment with high air humidity, resulting in charge separation and current output. However, most materials in existing wet gas power generation equipment have low adsorption efficiency for water molecules, resulting in a significant reduction in the power generation effect; and existing wet gas power generation materials, such as graphene and carbon nanotubes, are prone to structural aging or performance degradation under long-term humidity exposure conditions, resulting in a shortened service life of the equipment. There are a series of technical challenges in practical applications, which limit its further promotion.
[0004] Porous materials have abundant micropores and mesoporous structures, which can adsorb water molecules on the surface and inside of the material at the same time, effectively improving the moisture absorption efficiency. Based on such porous materials, wet gas generators can effectively promote the diffusion and transmission of water molecules inside the material by adsorbing water molecules in the air and forming a moisture gradient. In this process, the adsorption and diffusion of water molecules can trigger the charge separation on the surface or interface of the material, thereby driving the generation of current. Specifically, when the porous material absorbs moisture, the water molecules inside it interact with the surface of the material, resulting in charge accumulation or charge transfer. This interfacial charge transfer mechanism can not only significantly improve the efficiency of moisture conversion into electrical energy, but also overcome the limitations of traditional power generation equipment in the moisture collection process. Traditional wet gas power generation systems often rely on limited humidity differences to drive energy conversion, while porous materials can stably collect moisture under various humidity conditions and convert it into usable electrical energy through their highly developed pore structure and molecular-level moisture absorption characteristics. In this way, wet gas power generation technology based on porous materials breaks through the performance bottleneck of traditional wet gas power generation equipment, provides a more efficient and reliable wet gas energy collection solution, and adapts to more diverse application scenarios.
[0005] With the increase of social demand, wet gas power generation equipment used in a single environment can no longer meet the needs of energy collection in multiple scenarios. Therefore, how to prepare a wet gas generator that can work efficiently and have stable output in multiple environments through a simple and low-cost method is a current research hotspot. In order to achieve a wider range of applications, the development of wet gas generator technology that can be fast, stable, and has high conversion efficiency has become a research hotspot.
[0006] A humidity-controlled power generation gel and its preparation method and application are disclosed in the publication number CN116715804A. The invention discloses using LM-CD-PEG initiator to initiate monomer free radical polymerization, and preparing humidity-controlled power generation gel under the action of a crosslinker; the LM-CD-PEG initiator is a compound of gallium-indium alloy, β-cyclodextrin and polyethylene glycol, and the mass ratio of the LM-CD-PEG initiator, the crosslinker and the monomer is (18-20): (3-5): (30-50). This technical solution can form a stable humidity gradient in the natural environment, so that the device can generate electricity anytime and anywhere, but it has the disadvantages of slow humidity response speed, insufficient material stability, humidity range adaptability needs to be improved, and high manufacturing cost.
[0007] The disclosure discloses an ambient humidity power generation device and its preparation method with the publication number CN116015102A. The ambient humidity power generation device is composed of a substrate, a first electrode and a second electrode, a nanoporous material layer and a hydrogel layer. The hydrogel layer is spread on one end of the device, so that the end is rich in water, and the other end is directly in contact with the environment to form a stable humidity gradient, thereby realizing power generation anytime and anywhere. In addition, the hydrogel layer will also migrate to the nanoporous material layer, effectively reducing the internal resistance of the device and enhancing the power output effect. However, this technical solution has the defects of short humidity gradient maintenance time, limited adaptability, non-uniform distribution of the hydrogel layer caused by hydrogel migration, complex device structure, high manufacturing cost, and slow humidity response speed.
[0008] A layered wet gas generator and its preparation method with the publication number CN119051486A discloses a layered wet gas generator composed of an evaporation layer, a transmission layer and a water absorption layer stacked in sequence, wherein the evaporation layer and the water absorption layer are connected to electrodes respectively, and are used to collect the electric energy generated by wet gas power generation. The water absorption layer is composed of a water-absorbing gel (such as polystyrene sulfonic acid gel, polyvinyl alcohol gel, etc.), which can absorb moisture from the environment and provide a humidity gradient; the transmission layer is composed of a two-dimensional material (such as MXene, graphene oxide or black phosphorus) and a polyionic liquid, which is used for the directional transport of water molecules and ions; the evaporation layer is composed of a porous polyionic liquid, which is a portal for water molecules to exchange with the environment. Through this design, the wet gas generator realizes the efficient conversion of the chemical energy of water molecules into electrical energy, can continuously collect wet gas energy, and the device has excellent stability and reusability. However, there are still defects such as strong dependence on the wet environment, swelling problems of two-dimensional materials, controllability and cost problems of the preparation process, insufficient response performance in a dynamic humidity environment, potential degradation of reuse performance, and limited power generation voltage and energy output. Summary of the invention
[0009] In order to overcome the shortcomings of the prior art, the present invention provides a porous material for generating electricity using wet gas, and a preparation method and application thereof. The porous material and the wet gas generator based on the porous material have low preparation cost and simple process flow. The wet gas generator based on the porous material can achieve high current and voltage output, and the output performance can remain stable for a long time.
[0010] The technical solution of the present invention is a porous material for generating electricity using moisture, comprising a modified fabric coated with a mixture of MXene, PSS and xanthan gum.
[0011] The mass ratio of the MXene, PSS and xanthan gum is (5-16):(3-6):(0.5-3), preferably (8-9):(4-6):(1-3), and more preferably (8-9):(4-6):2.
[0012] The thickness of the modified fabric coated with the mixture of MXene, PSS and xanthan gum is 1 to 10 layers, preferably 3 to 6 layers, and more preferably 4 to 5 layers; the area of the modified fabric coated with the mixture of MXene, PSS and xanthan gum is 1 to 25 cm 2 , preferably 10 to 20 cm 2 , more preferably 12 to 16 cm 2 , more preferably 12-15cm 2 , more preferably 12-14cm 2 .
[0013] A method for preparing a porous material for generating electricity using moisture, comprising the steps of: immersing a fabric in a mixed solution containing MXene, PSS and xanthan gum, and drying the mixture to obtain a modified fabric coated with the mixture of MXene, PSS and xanthan gum.
[0014] In the mixed solution containing MXene, PSS and xanthan gum, the mass ratio of MXene, PSS and xanthan gum is (5-16):(3-6):(0.5-3), preferably (8-9):(4-6):(1-3), and more preferably (8-9):(4-6):2; the concentration of MXene is 2-7 mg / ml, preferably 3-6 mg / ml, and further preferably 4-5 mg / ml.
[0015] The preparation of the mixed solution containing MXene, PSS and xanthan gum comprises: respectively preparing a MXene solution, a PSS solution and a xanthan gum solution, mixing the MXene solution, the PSS solution and the xanthan gum solution, and preparing a mixed solution containing MXene, PSS and xanthan gum. Furthermore, firstly adding the PSS solution to the MXene solution, mixing evenly, then adding the xanthan gum solution, mixing until evenly, and preparing a mixed solution containing MXene, PSS and xanthan gum.
[0016] The preparation of the MXene solution includes: adding MXene to deionized water, and ultrasonically mixing to obtain a MXene solution with a concentration of 2 to 12 mg / mL, preferably 8 mg / mL.
[0017] The preparation of the PSS solution comprises: adding the PSS solution into deionized water to prepare a PSS solution with a concentration of 35 to 70 mg / mL, preferably 58 mg / ml.
[0018] The preparation of the xanthan gum solution comprises: adding xanthan gum into deionized water to prepare a xanthan gum solution with a concentration of 1 to 10 mg / mL, preferably 6 mg / ml.
[0019] The mixing is carried out by using a magnetic stirrer, the magnetic stirring time is 0.2 to 5 hours, and the stirring speed is 100 to 800 rpm.
[0020] The thickness of the fabric is 1 to 10 layers, preferably 3 to 6 layers, and more preferably 4 to 5 layers; the area of the fabric is 1 to 25 cm 2 , preferably 10 to 20 cm 2 , more preferably 12 to 16 cm 2 , more preferably 12-15cm 2 , more preferably 12-14cm 2 .
[0021] The porous material for generating electricity using moisture provided by the present invention can be used to prepare moisture power generation products, is suitable for generating electricity using moisture in various environments, and is suitable for collecting energy in various humidity environments.
[0022] The present invention provides a wet gas power generation product, which contains the porous material for generating electricity by utilizing wet gas provided by the present invention.
[0023] The invention also comprises electrodes, wherein the electrodes include a first electrode and a second electrode, both of which are inert metal electrodes. The first electrode and the second electrode are respectively connected to the upper surface and the lower surface of the porous material for generating electricity using moisture provided by the present invention to prepare a moisture power generation product.
[0024] The wet gas power generation products of the present invention include but are not limited to wet gas generators, wearable materials, devices or equipment, and materials, devices or equipment other than wearable materials.
[0025] When the wet gas generator prepared by the present invention is tested, it is placed in the middle of a porous electrode, one end is humidified and the other end is not humidified, so as to construct a humidity gradient.
[0026] It should be noted that MXene, as a material with excellent conductivity and surface activity, can form a composite structure with other materials to improve the performance of the wet gas generator. During the preparation process, the modified fabric after proper treatment forms a composite structure with good moisture responsiveness. This composite material can not only effectively adsorb moisture from the air, but also produce charge separation and convert it into electrical energy when water molecules interact with the surface of the material. In addition, the introduction of xanthan gum provides the composite material with enhanced mechanical strength and structural stability, while PSS enhances the electrical conductivity, thereby improving the electrical output performance during the wet gas power generation process. This preparation method is simple and low-cost, and at the same time, the final wet gas generator has excellent electrical and mechanical properties, which is suitable for energy collection in various humidity environments.
[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0028] (1) The present invention has low cost, simple operation process, excellent wet gas power generation performance, and is suitable for large-scale production and use.
[0029] (2) The wet gas generator based on porous materials prepared by the present invention has high output (such as current output 68μA, voltage output 0.84V), high output power (such as 57.12μw), and the output performance can remain stable for a long time.
[0030] (3) The wet gas generator prepared by the present invention can subsequently be transmitted via Bluetooth to achieve remote electrical output detection.
[0031] (4) After the solutions of MXene, PSS and xanthan gum are mixed, a synergistic effect is formed among the three. The hydroxyl groups in the xanthan gum molecules form hydrogen bonds with the groups in MXene and PSS. These interactions promote the composite effect between MXene, PSS and xanthan gum, thereby enhancing the compatibility and stability of the three.
[0032] Therefore, the present invention will further promote the practical application of the field of wet gas power generation materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the SEM image of the modified fabric prepared in Example 1.
[0034] Figure 2 This is a long-term output voltage test chart of the porous material-based wet gas generator prepared in Example 1.
[0035] Figure 3 This is a long-term output current test chart of the porous material-based wet gas generator prepared in Example 1.
[0036] Figure 4 This is a voltage-current diagram of the wet gas generator based on porous materials prepared in Example 1 switching wet gas.
[0037] Figure 5 This is a graph showing the voltage and current of the porous material-based wet gas generator prepared in Example 1 as it changes with temperature.
[0038] Figure 6 This is a test diagram of the output voltage of the porous material-based wet gas generator prepared in Example 1 after being connected in series and in parallel.
[0039] Figure 7 This is a test diagram of the output current of the wet gas generator based on porous materials prepared in Example 1 after being connected in parallel. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0041] The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications. The reagents and raw materials used in the present invention are all commercially available.
[0042] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available products or conventional processing techniques in the art.
[0043] Example 1
[0044] A method for preparing a wet gas generator based on porous materials, the specific steps of which are as follows:
[0045] (1) Add the PSS solution into deionized water to prepare a 58 mg / ml PSS solution;
[0046] (2) adding xanthan gum to deionized water to prepare a 6 mg / ml xanthan gum solution;
[0047] (3) MXene was prepared by liquid etching method, and deionized water was added to prepare 8 mg / ml MXene solution;
[0048] (4) taking 8 ml of the 8 mg / ml MXene solution of step (3) and mixing it with 0.24 ml of the 58 mg / ml PSS solution obtained in step (1) to prepare a MXene-PSS mixed solution;
[0049] (5) placing the MXene-PSS mixed solution of step (4) in a magnetic stirrer and stirring for 0.8 h to mix evenly;
[0050] (6) taking 5.9 ml of the 6 mg / ml xanthan gum solution of step (2) and mixing it with the MXene-PSS mixed solution obtained in step (5) to prepare a MXene-PSS-xanthan gum mixed solution, wherein the mass ratio of MXene, xanthan gum and PSS is about 9:5:2, and the concentration of MXene is about 4.5 mg / ml;
[0051] (7) placing the MXene-PSS-xanthan gum mixed solution described in step (6) in a magnetic stirrer and stirring for 3.5 h to mix evenly;
[0052] (8) Immersing the medical fabric in the MXene-PSS-xanthan gum mixed solution of step (7) and drying the mixture to obtain a modified fabric.
[0053] (9) Select a thickness of 4 layers and an area of 12 cm 2 A modified fabric, wherein a first electrode and a second electrode are connected to the upper surface and the lower surface of the modified fabric respectively, to obtain a wet gas generator based on a porous material, wherein the first electrode and the second electrode are both inert metal electrodes;
[0054] (10) One end of the porous material-based moisture generator is humidified, while the other end is not humidified, thereby constructing a humidity gradient.
[0055] The following tests were performed on the wet gas generator based on porous materials prepared in Example 1:
[0056] Figure 1 The SEM image of the modified fabric prepared in Example 1. The modified fabric sample was adhered to the sample stage by conductive adhesive, and the surface was sprayed with gold to observe the sample morphology. Figure 1 As shown, MXene was successfully attached to the modified fabric fibers (blue box).
[0057] The power generation performance of the wet gas generator based on porous materials prepared in Example 1 was tested using a Keithley 6514 digital source meter to read its output voltage and current values. Figure 2 to Figure 7 .in, Figure 2 This is a long-term output voltage test diagram of a wet gas generator based on porous materials prepared in Example 1. Figure 2 As shown in the figure, the long-term output voltage of the wet gas generator based on porous materials was tested, and the output voltage was 0.84V, and the sustainable output time was up to 6000s. During the long-term continuous use, the output voltage did not decrease significantly, proving the stability of its power generation performance.
[0058] Figure 3 This is a long-term output current test diagram of the wet gas generator based on porous materials prepared in Example 1. Figure 3 As shown in the figure, the long-term output current of the wet gas generator based on porous materials was tested, and the output current was 68μA, and the sustainable output time was up to 6000s. During long-term continuous use, the output current did not decrease significantly, proving the stability of its power generation performance.
[0059] Figure 4 This is a voltage-current diagram of the wet gas generator based on porous materials prepared in Example 1. Figure 4 As shown, after the humidity switch is opened and closed, the voltage output drops sharply from 0.84V to about 0.2V. Then, when the humidity switch is opened again, the voltage gradually returns to the original level of 0.84V, which indicates that the porous material-based moisture generator responds quickly to humidity.
[0060] Figure 5 The voltage and current diagram of the porous material-based wet gas generator prepared in Example 1 as a function of temperature. Figure 5 As shown, the electrical output first increases and then decreases with increasing temperature, showing the highest value between 30°C and 40°C. At the same relative humidity value, a decrease in temperature leads to a decrease in the H2O content, which can be attributed to the effect of temperature on the movement of charged particles in the modified fabric.
[0061] Figure 6 This is a test diagram of the output voltage of the porous material-based wet gas generator prepared in Example 1 after being connected in series. Figure 6As shown, the output voltage of the wet gas generator based on porous materials can be enhanced by connecting multiple devices in series. The output voltage of 2, 3, 4, and 5 devices in series can reach 1.6, 2.1, 2.6, and 2.9V, respectively.
[0062] Figure 7 This is a test diagram of the output current of the wet gas generator based on porous materials prepared in Example 1 after being connected in parallel. Figure 7 As shown, the output current of the wet gas generator based on porous materials can be enhanced by connecting multiple devices in parallel. The output current of 2, 3, 4, and 5 devices in parallel can reach 160, 209, 230, and 249 μA, respectively.
[0063] According to the process steps of Example 1, some process steps or process conditions were changed to form Examples 2 to 9 and Comparative Examples 1-2, and the specific settings are shown in Table 1. Except for the parameters recorded in Table 1, the other parameters of each Example or Comparative Example are the same as those of Example 1.
[0064] Table 1
[0065]
[0066]
[0067] The power generation performance of the device prepared above was tested using a Keithley 6514 digital source meter. The output voltage and current of the material are shown in Table 2.
[0068] Table 2
[0069] Example / Comparative Example Output voltage(V) Output current (μA) Example 1 0.84 68 Example 2 0.3 22 Example 3 0.6 40 Example 4 0.7 58 Example 5 0.45 42 Example 6 0.3 4.2 Example 7 0.68 26.5 Example 8 0.6 9.4 Example 9 0.5 3.8 Example 10 0.7 60 Embodiment 11 0.6 42 Comparative Example 1 0.2 5 Comparative Example 2 0.4 20
[0070] By comparing the experimental results of Examples 1-5, it can be seen that as the proportion of MXene increases, the voltage and current also increase. This is because MXene contains abundant oxygen-containing functional groups, which provide more hydrogen bonding sites, thereby adsorbing more water molecules as a positively charged material; and as the MXene content increases again, the electrical output decreases instead, because this may be caused by MXene aggregation.
[0071] By comparing the experimental results of Example 1 and Examples 6-8, it can be seen that as the number of layers increases, the thickness also increases, the voltage increases from 0.3V to 0.84V, and then decreases to about 0.6V, and the current increases from 4.2μA to 68μA, and then decreases to about 9.4μA. When the fabric layer is too thin, the ion concentration gradient is too small to allow ion movement; on the contrary, if the fabric layer is too thick, the diffusion path of ions in the internal nanochannels will be too long, thereby significantly reducing the diffusion efficiency of carriers.
[0072] By comparing the experimental results of Example 1 and Examples 9-11, it can be seen that as the area increases, the electrical output increases and reaches saturation. This may be because a small area of the generator is conducive to the transmission of charges, and a large area affects the collection of charges to a certain extent, resulting in a decrease in electrical output.
[0073] By comparing the experimental results of Example 1 and Comparative Example 1, it can be seen that MXene provides conductivity, while xanthan gum helps to bond and strengthen the structure, but lacks the components in PSS that enhance ionic conductivity, so the voltage and current outputs are lower.
[0074] Comparing the experimental results of Example 1 and Comparative Example 2, it can be seen that PSS provides ionic conductivity, but compared with the addition of xanthan gum, it lacks the effect of enhancing viscosity and increasing water adsorption, resulting in no significant increase in voltage. However, PSS has good conductivity and can effectively conduct the ionic current generated in the wet gas generator. The negative charge it carries may promote the separation of charges and increase the current output of the overall system.
[0075] It should be noted that the prior art in the protection scope of the present invention is not limited to the embodiments given in the present application documents. All prior art that does not contradict the scheme of the present invention, including but not limited to prior patent documents, prior public publications, prior public uses, etc., can be included in the protection scope of the present invention.
[0076] In addition, the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.
Claims
1. A porous material for generating electricity using moisture, characterized in that: Contains modified fabrics coated with a mixture of MXene, PSS and xanthan gum.
2. The porous material according to claim 1, characterized in that The mass ratio of the MXene, PSS and xanthan gum is (5-16):(3-6):(0.5-3).
3. The porous material according to claim 1 or 2, characterized in that: The thickness of the modified fabric coated with the mixture of MXene, PSS and xanthan gum is 1 to 10 layers, and the area of the modified fabric coated with the mixture of MXene, PSS and xanthan gum is 1 to 25 cm 2 .
4. The method for preparing a porous material according to any one of claims 1 to 3, characterized in that: The steps include: The fabric was immersed in a mixed solution containing MXene, PSS and xanthan gum and then dried.
5. The preparation method according to claim 4, characterized in that: In the mixed solution containing MXene, PSS and xanthan gum, the mass ratio of MXene, PSS and xanthan gum is (5-16):(3-6):(0.5-3), and the concentration of MXene is 2-7 mg / ml.
6. The preparation method according to claim 4 or 5, characterized in that: The thickness of the fabric is 1 to 10 layers, and the area of the fabric is 1 to 25 cm 2 .
7. The porous material according to any one of claims 1 to 3 is used for preparing wet gas power generation products.
8. A wet gas power generation product, characterized in that: The porous material comprises the porous material according to any one of claims 1 to 3.
9. A wet gas power generation product according to claim 8, characterized in that: Also contains electrodes.
10. A wet gas power generation product according to claim 8 or 9, characterized in that: Wet gas power generation products include at least one of the following: (1) Wet gas generator; (2) Wearable materials, devices or equipment; (3) Materials, devices or equipment other than wearables.
Citation Information
Patent Citations
Environmental humidity power generation device and preparation method thereof
CN116015102A
Humidity power generation gel and preparation method and application thereof
CN116715804A
Layered moisture generator and preparation method thereof
CN119051486A